Gender differences in financial reporting decision-making: Evidence from accounting conservatism - Bill Francis; Iftekhar Hasan; Qiang Wu; Jong Chool Park (Bank of Finland, 2014)
This paper investigates the effect of CFO gender on corporate financial reporting decision-making. Focusing on firms that experience changes of CFO from male to female, the paper compares the firms' degree of accounting conservatism between pre- and post-transition periods. We find that female CFOs are more conservative in their financial reporting. In addition, we find that the relation between CFO gender and conservatism varies with the levels of various firm risks such as litigation risk, default risk, systematic risk, and CFO specific risk such as job security risk. We further find that risk-aversion of female CFOs is associated with less equity-based compensation, lower firm risk, higher tangibility level, and lower dividend payout level. Overall, the study provides strong support for the notion that female CFOs are more risk averse than male CFOs, which leads female CFOs to adopt more conservative financial reporting policies.
URN:NBN:fi:bof-20140807332
Keywords: M41; J16; 330; Accounting Conservatism; Gender; CFO; Risk-Aversion